Molecular phylogeny of Metanoeina net-winged beetles identifies Ochinoeus, a new genus from China and Laos (Coleoptera: Lycidae) - Kubecek, Vaclav; Bray, Timothy C; Bocak, Ladislav (Zootaxa, 2015)
The molecular hypothesis on relationships of Metanoeina lineages is presented and results are compared with morphology. A new genus Ochinoeus is proposed for four East Palearctic and Oriental species. Ochinoeus is recovered as a sister lineage to Matsudanoeus Sklenarova et al., 2014 and differs from related genera in morphology of genitalia and incomplete secondary elytral costae. We show, that the structure of elytral costae, although highly homoplastic across Metriorrhynchini, can be used for identification of Ochinoeus. The geographic distribution of Metanoeina is limited to the eastern parts of the Palaearctic and Oriental regions. The reconstruction of ancestral ranges identifies continental Eastern Asia as the centre of generic diversity of Metanoeina and suggests the dispersal from continental Asia to the southern part of the Oriental region, i.e. to the Sundaland and Philippines. Among Metanoeina lineages, only Metanoeus Waterhouse, 1878 contains higher number of species. The following four species are described: Ochinoeus huaphanensis sp. nov., O. hainanensis sp. nov., O. habashanensis sp. nov., and O. xunyanbaensis sp. nov..
Keywords: Čína; brouci; Body Size; ekosystém; velikost těla; mužské pohlaví; rozšíření zvířat; China; Organ Size; velikost orgánu; ženské pohlaví; zvířata; anatomické struktury zvířat; Coleoptera; fylogeneze; Laos; Animal Distribution; Female; Ecosystem; Phylogeny; Animal Structures; Male; Animals